Entrepreneurship in the public sector when middle managers create public value - Diefenbach, Fabian E. (Springer eBooks., 2011)
Entrepreneurship is often considered one way for public sector organizations to better serve the public. But what are the drivers for entrepreneurship in such organizations? And does entrepreneurship really create value? To answer these questions, Fabian E. Diefenbach develops a research model based on a comprehensive review of the literatures on private sector corporate entrepreneurship, public entrepreneurship, and public value management. The empirical analyses identify five drivers of entrepreneurship and show a positive effect of entrepreneurship on value creation. This book concludes with a detailed discussion of the results and, importantly, their implications for public sector managers.